Development of high content imaging methods for cell death detection in human pluripotent stem cell-derived cardiomyocytes - Mioulane,M; Foldes,G; Ali,NN; Schneider,MD; Harding,SE (Journal of Cardiovascular Translational Research, 2012)
Human pluripotent stem cell-derived cardiomyocytes (hPSC-CM) are being investigated as a new source of cardiac cells for drug safety assessment. We developed a novel scalable high content microscopy-based method for the detection of cell death in hPSC-CM that can serve for future predictive in vitro cardio-toxicological screens. Using rat neonatal ventricular cardiomyocytes (RVNC) or hPSC-CM, assays for nuclear remodelling, mitochondrial status, apoptosis and necrosis were designed using a combination of fluorescent dyes and antibodies on an automated microscopy platform. This allowed the observation of a chelerythrine-induced concentration-dependent apoptosis to necrosis switch and time-dependent progression of early apoptotic cells towards a necrotic-like phenotype. Susceptibility of hPSC-CM to chelerythrine-stimulated apoptosis varied with time after differentiation, but at most time points, hPSC-CM were more resistant than RVNC. This simple and scalable humanized high-content assay generates accurate cardiotoxicity profiles that can serve as a base for further assessment of cardioprotective strategies and drug safety.